Does inappropriate prescription affect elderly patients’ quality of life? A study from a Malaysian tertiary hospital - Akkawi, Muhammad Eid; Nik Mohamed, Mohamad Haniki; Md Aris, Mohd Aznan (Springer International Publishing, 2019)
To investigate the association between potentially inappropriate medication (PIM)/potential prescribing omission (PPO) and the health-related quality of life (HRQoL) among community-dwelling hospitalized elderly patients. Methods This is a cross-sectional study that took place in a Malaysian tertiary hospital. Patients ≥ 65 years old with at least one medication on admission were recruited. The patients’ prehospitalization medications were reviewed to identify PIMs/ PPOs using version 2 of the STOPP/START criteria. HRQoL was assessed using the EuroQol-5 dimensions (EQ-5D) and EuroQol-visual analog scale (EQ-VAS). The association between the presence of PIM/PPO and the patients’ HRQoL was analyzed using Chi-square and Mann–Whitney U tests. Multiple linear regression models were applied to determine the effect of exposure to PIM/PPO on the patients’ HRQoL, adjusting for confounders. Results Out of 517 patients who fulfilled the inclusion criteria, 502 patients (97%) accepted to be involved in the study and completed the HRQoL questionnaire. The mean (SD) age was 72.4 (5.9) years. 393 (78.3%) of the patients had problems in at least one EQ-5D dimension with pain/discomfort problem being the most reported complaint. The mean (SD) values of the EQ-5D index and the EQ-VAS were 0.734 (0.214) and 59.6 (14.2), respectively, which are lower than those seen in the general Malaysian population. PIM and PPO were found in 28.5% and 45.6% of the patients, respectively. No significant differences were found in the EQ-5D dimensions, EQ-5D index and EQ-VAS between patients who had PIM/PPO and those who did not. Age, sex, and comorbidities were significantly associated with the patients’ HRQoL. Conclusion PIM and PPO are not uncommon among hospitalized elderly patients; however, it does not significantly affect their HRQoL as measured by the EQ-5D-3L instrument.